Asymmetry and Systemic Misperception: China, Vietnam and Cambodia during the 1970s. - Womack, Brantly (Journal of Strategic Studies, 2003)
The purpose of this article is to set forth a basic structural model for analyzing asymmetric dyads. It begins with patterns of attention and behavior related to disparity. It then considers characteristic, complementary patterns of systemic misperception arising from the different poles of the dyad and the moderating forces that constrain misperception. Finally, cases will be analyzed that are indisputably asymmetric and that present extreme illustrations of the model. Many interesting and vexed questions of international relations and of social science in general touch on this discussion.